Enhancing Teacher Competence through a Workshop on Developing Ethnophysics-Based Teaching Modules - Winny Liliawati; Agus Danawan; Harun Imansyah; Iyon Suyana; Rizki Zakwandi; Nurdini Nurdini; M. Reza Dwi Saputra (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2024)
This study aims to describe the implementation of a workshop on developing Ethnophysics-based teaching modules as part of a community service program. The workshop was conducted to enhance the ability of Physics teachers to develop teaching modules relevant to local cultural contexts, making Physics learning in schools more contextual and meaningful. The workshop was held online, combining synchronous and asynchronous learning through a video conferencing platform and a Learning Management System (LMS). A descriptive qualitative method was used to analyze data from 97 participating teachers from various provinces in Indonesia. The instruments included questionnaires to understand teachers' profiles and perceptions of teachers in developing Ethnophysics-based teaching modules, and participant worksheets to identify knowledge and local cultural practices relevant to physics concepts. The results from teachers' perceptions of Ethnophysics indicate that most teachers require guidance in understanding and developing Ethnophysics-based teaching modules. The outcomes of this community service activity also show that teachers were able to identify and plan Ethnophysics-based teaching modules appropriate to the local wisdom of their respective regions. These findings serve as a foundation for developing more structured mentoring programs for high school teachers to support their competencies in applying Ethnophysics in teaching. Keywords: ethnophysics; teaching modules; community service program